The art of simple living 100 daily practices from a Japanese Zen monk for a lifetime of calm and joy - Masuno, Shunmyo&#772 (New York Penguin Books, 2019)
In this book you will learn 100 ways to bring yoursrlf true happiness and calm. You will learn how to exhale deeply to eliminate negative emotions, to arrange your house simply to clear your thinking, to line up your shoes at night to bring order to your mind, to plant a single flower and watch it grow, to worry less about what you cannot control.
Keywords: Spiritual life--Zen Buddhism